The Influence of Work Environment and Compensation on Employee Job Satisfaction at Al Syukro Universal Ciputat - Indri Guslina; Syamsudin Syamsudin; Kushardanta Susilabudi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to determine how much influence the work environment and compensation have on employee job satisfaction at Al Syukro Universal Islamic College Ciputat. This study was conducted at Al Syukro Universal Ciputat. This study uses a quantitative approach. The sampling technique, namely the random sampling method in this study is a technique for determining samples from the population carried out randomly without considering the strata in the population. The data collection technique uses observation in the form of a questionnaire. The data processing techniques used in this study are validity tests, reliability tests, multiple linear regression tests, determination coefficients, and simultaneous tests. The variables of the work environment (X1), compensation (X2), job satisfaction (Y), the results of the validity test have a CITC value greater than 0.30. The results of the study are a significant level of P-value (0.000) <0.05, which means that there is an influence between the work environment and job satisfaction, which is 61.2%. Meanwhile, compensation for job satisfaction also has an influence of 46.5%, which means that there is an influence between the work environment and compensation, namely 66.8%, while the remaining 33.2% is influenced by other variables that were not examined in this study.